Determinants of Innate Immunity in Visceral Leishmaniasis and Their Implication in Vaccine Development - Volpedo, Greta; Pacheco-Fernandez, Thalia; Bhattacharya, Parna; Oljuskin, Timur; Dey, Ranadhir; Gannavaram, Sreenivas; Satoskar, Abhay R.; Nakhasi, Hira L. (Frontiers in Immunology, 2021)
Leishmaniasis is endemic to the tropical and subtropical regions of the world and is transmitted by the bite of an infected sand fly. The multifaceted interactions between Leishmania, the host innate immune cells, and the adaptive immunity determine the severity of pathogenesis and disease development. Leishmania parasites establish a chronic infection by subversion and attenuation of the microbicidal functions of phagocytic innate immune cells such as neutrophils, macrophages and dendritic cells (DCs). Other innate cells such as inflammatory monocytes, mast cells and NK cells, also contribute to resistance and/or susceptibility to Leishmania infection. In addition to the cytokine/chemokine signals from the innate immune cells, recent studies identified the subtle shifts in the metabolic pathways of the innate cells that activate distinct immune signal cascades. The nexus between metabolic pathways, epigenetic reprogramming and the immune signaling cascades that drive the divergent innate immune responses, remains to be fully understood in Leishmania pathogenesis. Further, development of safe and efficacious vaccines against Leishmaniasis requires a broader understanding of the early interactions between the parasites and innate immune cells. In this review we focus on the current understanding of the specific role of innate immune cells, the metabolomic and epigenetic reprogramming and immune regulation that occurs during visceral leishmaniasis, and the strategies used by the parasite to evade and modulate host immunity. We highlight how such pathways could be exploited in the development of safe and efficacious Leishmania vaccines.